Existence and compactness of solution of semilinear integro-differential equations with finite delay - Sahraoui, F.; Ouahab, А. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.9We present some existence and uniqueness results for a class of functional integro-differential evolution equations  generated by the resolvent operator for which the semigroup is not necessarily compact. It  is proved that the set of solutions is compact.  Our approach is based on fixed point theory.  Finally, some examples are given to illustrate the results.